Towards a Healthy Generation Through Stunting Counseling for a Bright Future - Wuri Andini; Lilif Mualifatul Khorida Filasofa (Universitas Palangka Raya, 2024)
A complex and serious public health problem, stunting is more common in children who are malnourished during their growing years. The main causes include a lack of consumption of nutrient-dense foods, an unclean environment, and a lack of knowledge about the importance of optimal nutrition. According to health reports, the percentage of stunted population in Kendal District increased from 17.5% in 2022 to 22.4% in 2023. In addition to impacting long-term health, productivity, and cognitive function, stunting also affects physical growth. To address this issue, a cross-sectoral strategy is needed that includes improved health services, community education, and provision of high-nutrient supplementary foods. On this occasion, two midwives served as presenters in a socialization session aimed at raising the awareness of mothers about stunting and the importance of nutrition in Cepokomulyo village.